Analisis Kualitas Website Menggunakan Model Webqual 4.0 : Studi Kasus: Website Spekma Universitas Nahdlatul Ulama Sunan Giri Bojonegoro - Ananda Devi Muri Utomo; Arista Pratama; Erista Maya Safitri (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
The rapid development of technology and communication has had a major influence on human life, making it easier to access information such as websites. The role of a website is very important for success, especially in higher education. Based on this, Nahdaltul Ulama Sunan Giri Bojonegoro University built a student credit point system (SPEKMA) where this system is able to make it easier to save credit point values ​​for each activity that is determined based on an assessment of the achievements and activities that have been achieved by a student. The aim of this research is to determine the quality of the student credit points system (SPEKMA) website using the Webqual 4.0 model and Importance Performance Analysis (IPA). This research uses Webqual as the basis for creating a questionnaire and Importance Performance Analysis (IPA) as an analytical tool in the form of Gap Analysis and Cartesian quadrants. This research used proportionate stratified random sampling with a total of 91 respondents who were active students at Nahdaltul Ulama Sunan Giri University, Bojonegoro. Based on the results obtained, it shows that the overall quality of the SPEKMA website of Nahdlatul Ulama Sunan Giri Bojonegoro University is not quite in line with user expectations. This is evident from the calculation results that the information quality variable results in a negative GAP gap (where the average importance value is greater than the average performance) with an average importance value of 4.12, an average performance value of 4.08. There are indicators that do not meet the interests and expectations of users.